2022
DOI: 10.3389/fpsyt.2022.883517
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Framework for Assessing Cannabis-Related Impairment Risk

Abstract: Clinicians play an important role in promoting safe and responsible medical cannabis use. One essential component to safe use is considering a patient's risk of neurocognitive impairment. However, there remains a lack of practical guidance on how clinicians can evaluate this risk for medical cannabis patients. Here, a practical framework is presented for clinicians to assess and stratify cannabis-associated impairment risk. The proposed framework is intended to practically guide healthcare providers in gaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…This is particularly evident in chronic cannabis users who exhibit fewer neurocognitive deficits compared to infrequent users ( Ramaekers et al, 2009 ). Existing research supports these findings, albeit derived primarily from self-reported evidence, which suggests a therapeutic role for medical cannabis in managing clinical symptoms commonly associated with cognitive and psychomotor impairment ( Eadie et al, 2021 ; MacCallum et al, 2022 ). Specifically, patients who routinely administer medical cannabis for chronic conditions may develop a tolerance to the prototypical THC-induced impairments in driving abilities that are more pronounced in occasional or inexperienced users, thereby potentially reducing the impact of THC on driving competency seen in otherwise healthy subjects ( Celius and Vila, 2018 ; Freidel et al, 2015 ; Veldhuijzen et al, 2006 ).…”
Section: Discussionmentioning
confidence: 89%
“…This is particularly evident in chronic cannabis users who exhibit fewer neurocognitive deficits compared to infrequent users ( Ramaekers et al, 2009 ). Existing research supports these findings, albeit derived primarily from self-reported evidence, which suggests a therapeutic role for medical cannabis in managing clinical symptoms commonly associated with cognitive and psychomotor impairment ( Eadie et al, 2021 ; MacCallum et al, 2022 ). Specifically, patients who routinely administer medical cannabis for chronic conditions may develop a tolerance to the prototypical THC-induced impairments in driving abilities that are more pronounced in occasional or inexperienced users, thereby potentially reducing the impact of THC on driving competency seen in otherwise healthy subjects ( Celius and Vila, 2018 ; Freidel et al, 2015 ; Veldhuijzen et al, 2006 ).…”
Section: Discussionmentioning
confidence: 89%
“…Unlike CBD, THC is well known for its increased risk of impairment [ 44 , 45 ], particularly when combined with other sedatives [ 20 ]. Nonetheless, our analyses revealed that patients on prescribed opioids and/or antipsychotics, drugs with sedating properties, are significantly more likely to be receiving THC-dominant or T+C products (70%) than CBD-dominant (30%) products, OR = 2.2 (1.0,4.6); perhaps suggesting a failure to investigate safer alternatives or inadequate attention to potential drug-drug interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, our analyses revealed that patients on prescribed opioids and/or antipsychotics, drugs with sedating properties, are significantly more likely to be receiving THC-dominant or T+C products (70%) than CBD-dominant (30%) products, OR = 2.2 (1.0,4.6); perhaps suggesting a failure to investigate safer alternatives or inadequate attention to potential drug-drug interactions. Conversely, the primary concern with CBD is its risk of interaction with CYP450 metabolised drugs, particularly those engaging CYP3A4, CYP2C9 and CYP 2C19 [ 20 , 21 , 44 , 46 , 47 ]. CYP3A4 enzymes [ 21 ] are responsible for the metabolism of benzodiazepines including alprazolam, midazolam and clobazam; and for part of the metabolism of other benzodiazepines including diazepam and flutrinazepam [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Guidance from healthcare providers is all the more important given information found on the internet directed at medical cannabis consumers may be biased 66–68. In discussing cannabis use with this group of workers, healthcare providers may consider drawing from a recent clinical framework for assessing impairment risk from medical cannabis 69…”
Section: Discussionmentioning
confidence: 99%